A New Dinoflagellate Genome Illuminates a Conserved Gene Cluster Involved in Sunscreen Biosynthesis. (4th November 2020) - Shoguchi, Eiichi; Beedessee, Girish; Hisata, Kanako; Tada, Ipputa; Narisoko, Haruhi; Satoh, Noriyuki; Kawachi, Masanobu; Shinzato, Chuya
Abstract: Photosynthetic dinoflagellates of the Family Symbiodiniaceae live symbiotically with many organisms that inhabit coral reefs and are currently classified into fifteen groups, including seven genera. Draft genomes from four genera, Symbiodinium, Breviolum, Fugacium, and Cladocopium, which have been isolated from corals, have been reported. However, no genome is available from the genus Durusdinium, which occupies an intermediate phylogenetic position in the Family Symbiodiniaceae and is well known for thermal tolerance (resistance to bleaching). We sequenced, assembled, and annotated the genome of Durusdinium trenchii, isolated from the coral, Favia speciosa, in Okinawa, Japan. Assembled short reads amounted to 670 Mb with ∼47% GC content. This GC content was intermediate among taxa belonging to the Symbiodiniaceae. Approximately 30, 000 protein-coding genes were predicted in the D. trenchii genome, fewer than in other genomes from the Symbiodiniaceae. However, annotations revealed that the D. trenchii genome encodes a cluster of genes for synthesis of mycosporine-like amino acids, which absorb UV radiation. Interestingly, a neighboring gene in the cluster encodes a glucose–methanol–choline oxidoreductase with a flavin adenine dinucleotide domain that is also found in Symbiodinium tridacnidorum . This conservation seems to partially clarify an ancestral genomic structure in the Symbiodiniaceae and its loss in late-branching lineages, including Breviolum and Cladocopium, after splitting from the Durusdinium lineage. Our analysis suggests that approximately half of the taxa in the Symbiodiniaceae may maintain the ability to synthesize mycosporine-like amino acids. Thus, this work provides a significant genomic resource for understanding the genomic diversity of Symbiodiniaceae in corals.